Interplay of phosphorus and Piriformospora indica in attenuating aluminium stress in barley and other plants: Recent developments and phytoremediation strategies - Ibrahim, Zakir; Sehar, Shafaque; Adil, Muhammad Faheem; Hung, Patricia King Jie; Ullah, Najeeb; Wang, Lanlan; Shamsi, Imran Haider (Elsevier, 2025)
Aluminium (Al) toxicity is a pervasive environmental issue in acidic soils, adversely affecting plant health and crop yields globally. Soil pH below 5.5 solubilizes aluminium as the toxic Al3+ ion, impairing root growth and function, leading to stunted plants and reduced crop productivity. This problem is particularly severe in regions with high rainfall such as the tropics and subtropics. Understanding and mitigating Al toxicity is essential for agricultural sustainability. Barley (Hordeum vulgare L.), a crop highly sensitive to Al toxicity, serves as an excellent model for studying this phenomenon due to its economic significance and susceptibility to soil acidity. Recent research has highlighted the critical role of beneficial soil microorganisms in mitigating Al toxicity. Specifically, Piriformospora indica, an endophytic fungus, has shown promise in enhancing plant tolerance to Al stress through mechanisms such as organic acid production, which chelates Al3+ ions, and the activation of antioxidant defenses. Studies have demonstrated that P. indica can significantly improve root growth, nutrient uptake, and plant vigor in barley under Al stress. The review discusses the genetic and molecular responses involved, including the upregulation of genes related to antioxidant defense and nutrient transport. Furthermore, the review compares the effects of P. indica on barley with other crops and explores its synergistic interactions with additional nutrients, such as phosphorus. This review aims to synthesize current knowledge on Al toxicity mechanisms in barley, the capacity of P. indica to mitigate this stress, and future research directions. By exploring the intersection of plant physiology, microbiology, and soil science, the review seeks to support the advancement of sustainable farming practices that mitigate Al toxicity, ultimately promoting food security and environmental health.